Towards a more balanced view of marine ecosystems. (24th November 2012) - Greene, Charles H.
Abstract Frank et al. (Nature, 477, 2011, 86) hypothesize that the slow recovery of the Scotian Shelf ecosystem to its structure prior to the early 1990s is a result of the oscillatory, runaway consumption dynamics of the forage fish complex. Their hypothesis is based on the underlying assumptions that this ecosystem's dynamics are governed by top‐down forcing, predator–prey role reversals, and a trophic cascade extending from demersal predatory fish, especially cod, down to the level of nutrients (Science, 308, 2005, 1621; Nature, 477, 2011, 86). Greene and Pershing (Science, 315, 2007, 1084) called into question the underlying assumption of an extended trophic cascade. They argued that while top‐down forcing can be important at higher trophic levels in many Northwest Atlantic Shelf ecosystems, its impacts on zooplankton, phytoplankton, and nutrients are minor or nonexistent. Instead, they argued that lower trophic‐level dynamics in these ecosystems are governed by climate‐associated, bottom‐up forcing. Observations over the past three decades (Greene et al. Ecology, 89, (Suppl 11), 2008, S24; MERCINA Oceanography, 25, 2012, 208.) are consistent with predictions from the climate‐forcing hypothesis proposed by Greene and Pershing (Science, 315, 2007, 1084), while those from the past decade (MERCINA, Oceanography, 25, 2012, 208) demonstrate that the trophic cascade hypothesis as proposed by Frank et al. (Science, 308, 2005, 1621) should be rejected. A closer examination of these observations also calls into question the hypothesis of ecosystem recovery in the Northwest Atlantic being governed by the oscillatory, runaway consumption dynamics of the forage fish complex.